2005
DOI: 10.1523/jneurosci.1808-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Phagocytosis Induced by Fibrillar β-Amyloid and IgGs Are Differentially Regulated by Proinflammatory Cytokines

Abstract: Microglia undergo a phenotypic activation in response to fibrillar ␤-amyloid (fA␤) deposition in the brains of Alzheimer's disease (AD) patients, resulting in their elaboration of inflammatory molecules. Despite the presence of abundant plaque-associated microglia in the brains of AD patients and in animal models of the disease, microglia fail to efficiently clear fA␤ deposits. However, they can be induced to do so during A␤ vaccination therapy attributable to anti-A␤ antibody stimulation of IgG receptor (FcR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
342
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(370 citation statements)
references
References 90 publications
(105 reference statements)
21
342
2
5
Order By: Relevance
“…It has been proposed that clearance or deposition of Aβ peptide may be determined by factors such as Aβ peptide burden and the duration of cell exposure [43]. Interestingly it has been reported that proinflammatory cytokines reduces the function of the phagocytic machinery of microglia, which can be relieved by anti-inflammatory cytokines, suggesting a possible strategy for the treatment of AD [45].…”
Section: Unanswered Questions In Alzheimer's Diseasementioning
confidence: 99%
“…It has been proposed that clearance or deposition of Aβ peptide may be determined by factors such as Aβ peptide burden and the duration of cell exposure [43]. Interestingly it has been reported that proinflammatory cytokines reduces the function of the phagocytic machinery of microglia, which can be relieved by anti-inflammatory cytokines, suggesting a possible strategy for the treatment of AD [45].…”
Section: Unanswered Questions In Alzheimer's Diseasementioning
confidence: 99%
“…Microglia are competent phagocytes and normally clear A␤ from the brain (22,43). However, inflammatory cytokines, which are present at elevated levels in the AD brain, suppress the phagocytic activity of these cells.…”
Section: Lxrs Couple Their Antiinflammatory Activity To Increased Phamentioning
confidence: 99%
“…Despite decorating amyloid plaques, microglia in the AD brain are poor phagocytes of deposited amyloid. This phenomenon has been proposed to be due in part to inhibition of their phagocytic capacity by the chronic inflammatory milieu (22). Interestingly, antiinflammatory drugs are able to reverse this defect in phagocytosis, suggesting that modulating microglial activation may promote amyloid clearance.…”
mentioning
confidence: 99%
“…Glucocorticoids are crucial for the proper control of an immune response, therefore preventing their production by inhibiting COX-2 can lead to a heightened inflammatory response, especially in the CNS. 91 It has also been recently shown that COX-2 inhibition 92 and prostaglandin E 2 receptor ablation 93 increases b-amyloid phagocytosis by microglial cells, although the mechanisms mediating these actions remain unknown. We must therefore be careful in the interpretation of clinical trials involving the use of NSAIDS for the treatment of neurodegenerative disorders such as AD, since it may in fact be an increased immune response or an increased phagocytic activity in the CNS that is responsible for the protective effects of these drugs.…”
Section: Innate Immunity and Alzheimer's Diseasementioning
confidence: 99%